Cytokinin Regulation of Source-Sink Relationships in Plant-Pathogen Interactions - McIntyre, Kathryn E.; Bush, Daniel R.; Argueso, Cristiana T. (Frontiers in Plant Science, 2021)
Cytokinins are plant hormones known for their role in mediating plant growth. First discovered for their ability to promote cell division, this class of hormones has now been associated with many other cellular and physiological functions. One of these functions is the regulation of source-sink relationships, a tightly controlled process that is essential for proper plant growth and development, and as discovered more recently, also important for the interaction between plants and pathogens. Here we review the physiological process of source-sink relationships in plants, with relation to both carbohydrates and amino acids, and highlight evidence suggesting points of control by cytokinin. We finish by highlighting the importance of source-sink relationships for the outcome of plant-pathogen interactions, indicating a possible role for cytokinins in this process.